Resting-state spontaneous fluctuations in brain activity: a new paradigm for presurgical planning using fMRI. - Shimony JS; Zhang D; Johnston JM; Fox MD; Roy A; Leuthardt EC; Shimony, Joshua S; Zhang, Dongyang; Johnston, James M; Fox, Michael D; Roy, Abhik; Leuthardt, Eric C (Academic Radiology, 2009)
Rationale and Objectives: Task-evoked functional MRI (fMRI) has been used successfully in the study of brain function and clinically for presurgical localization of eloquent brain regions prior to the performance of brain surgery. This method requires patient cooperation and is not useful in young children or if the patient has cognitive dysfunction or physical impairment. An alternative method that can overcome some of these disadvantages measures the intrinsic function of the brain using resting-state fMRI. This method does not require any task performance and measures the spontaneous low-frequency (<0.1 Hz) fluctuations of the fMRI signal over time. Our objective in the present work is to provide preliminary information on the possible clinical utility of this technique for presurgical planning and on possible future applications.Materials and Methods: Data from prior fMRI resting-state studies were reviewed for their potential use in preoperative mapping. Structural and resting-state fMRI data from normal subjects and patients with brain tumors were preprocessed and seed regions were placed in key regions of the brain; the related functional networks were identified using correlation analysis.Results: Several key functional networks can be identified in patients with brain tumors from resting-state fMRI data.Conclusion: Resting-state fMRI data can provide valuable presurgical information in many patients who cannot benefit from traditional task-based fMRI. Adoption of this method has the potential to improve individualized patient-centered care.